Cassava Based Substrates - Conducive Media for Mass Multiplication of Trichoderma asperellum - Viji, VS; Veena, SS; Karthikeyan, S; Jeeva, ML (JOURNAL OF ROOT CROPS, 2018)
Biological control is considered as a sustainable practice for efficient management of notorious pathogens, especially soil borne pathogens. Trichoderma species have long been recognized as agents for the control of plant disease and for their ability to increase plant growth and development. Tropical tuber crops are rich in carbohydrate and serve as staple food for millions of people in different parts of the world. These crops are attacked by different groups of plant pathogens. Application of Trichoderma is being recommended for the management of many fungal diseases in tuber crops viz., tuber rot in cassava, collar rot in elephant foot yam, taro leaf blight and anthracnose in yams. In the present study, cassava rind, cassava powder, cassava tuber extract, cassava leaf waste obtained after extraction of cassava bio-pesticide, coconut water, rice starch water, vermicompost, dolomite and potato dextrose broth (PDB) were evaluated for their suitability to be used as substrates for multiplication of Trichoderma spp. Ten substrates were inoculated with Trichoderma and increase in the population was monitored at 4, 6, 8, 10 and 12 days after inoculation by adopting serial dilution technique. The highest population of Trichoderma was recorded in vermicompost (1.33 x1040 cfug-1 substrate) followed by cassava powder and coconut water. High population was noted in other cassava based substrates viz., cassava rind (6.0 x1026 cfug-1 substrate), cassava tuber extract (1.33 x1032 cfug-1 substrate) and cassava leaf waste obtained after extraction of bio-pesticide (2.63 x1029 cfug-1 substrate). The present study reveals the potential of cassava based substrates for the mass multiplication of Trichoderma.